Hepatic Dysfunction in Dengue Fever: Prevalence, Patterns, and Clinical Correlation - Khan, Zahid Ullah; Batool, Rabia; Khan, Rana Taimoor Ahmad; Shaikh, Muhammad Tamoor Akhtar; Sabeeh Ul Haq, Mohammad; Begum, Labina (Indus Journal of Bioscience Research, 2025)
Background: Dengue fever, caused by the dengue virus (DENV), is a common tropical and subtropical viral infection that can lead to a range of complications, including hepatic dysfunction. Objective: This study aimed to investigate the prevalence, severity, and clinical implications of hepatic dysfunction in patients diagnosed with dengue fever, focusing on its association with disease severity, complications, and clinical outcomes. Methods: This retrospective study was conducted at Lady Reading Hospital Peshawar over a period of 6 months, involving 135 patients diagnosed with dengue fever to investigate the prevalence, patterns, and clinical correlations of hepatic dysfunction. Demographic, clinical, and laboratory data were collected from patient records, including liver function tests (ALT, AST, total bilirubin) and platelet counts. Hepatic dysfunction was categorized as mild, moderate, or severe based on liver enzyme levels. Results: Hepatic dysfunction was observed in 53.3% of patients, with mild dysfunction in 31.1%, moderate dysfunction in 13.3%, and severe dysfunction in 8.9%. Severe hepatic dysfunction was significantly associated with severe dengue (p < 0.05). Patients with severe hepatic dysfunction had higher rates of complications, including bleeding (50%), shock (41.7%), and multi-organ failure (16.7%). A significant negative correlation was found between platelet count and the severity of hepatic dysfunction (p < 0.05). The mortality rate was 3.7%, with all fatalities occurring in patients with severe hepatic dysfunction and multi-organ failure. Conclusions: Hepatic dysfunction is a common and clinically significant complication of dengue fever, particularly in severe cases. The severity of liver involvement is strongly correlated with disease severity and adverse clinical outcomes, including complications and increased mortality.